APPROPRIATE PACKAGING INNOVATION TO INCREASE THE COMPETITIVENESS AND SELLING VALUE OF LOCAL FOOD IN BOJONGKUNCI VILLAGE, BANDUNG REGENCY - Dendi Gusnadi; Tito Pandu Raharjo; Dika Dwi Panji (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Local food is one of the economic potentials of the village that has high cultural and sustainable value. However, the lack of innovation in the packaging aspect is the main obstacle in increasing the competitiveness and selling value of these products. This research aims to design and implement appropriate packaging innovations that are in accordance with the characteristics of local food products in Bojongkunci Village, Bandung Regency. The methods used include a participatory approach through training, group discussions, and packaging design trials with local business actors. The results of the activity show that the use of ergonomic, informative, and aesthetic packaging is able to increase consumer buying interest, expand market reach, and strengthen the identity of local products. This packaging innovation also contributes to increasing the income of micro business actors and supports the sustainable development of the village economy.